Efektivitas Ultrasound Dan Massage Pada Penyakit Myofacial Pain Syndrome Pada Trapezius Upper: Literatur Review - Hilmi Rozaan N; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
In the field of musculoskeletal rehabilitation, the quality of physiotherapy in the treatment of myofascial pain syndrome (MPS) is crucial because it influences the effectiveness of therapy and patient satisfaction. If we want to improve the quality of care, it is crucial to understand the effectiveness of various therapy methods. This literature review summarizes studies that have been conducted to evaluate how ultrasound and deep tissue massage (also known as deep tissue massage) reduce pain and musculoskeletal function in patients with MPS. In a study by Chen et al. (2025), ultrasound-guided myofascial hydrodissection (UMHT) was found to be comparable in effectiveness to 1% lidocaine trigger point injection. Both methods have been shown to reduce pain and improve function without significant side effects. However, a study by Bingölbali et al. found that deep tissue massage (DTM) significantly reduced pain, increased range of motion (ROM), and improved quality of life compared to a control group. Overall, these two studies demonstrate that non-pharmacological methods such as ultrasound-guided therapy and deep tissue massage are effective and safe methods for musculoskeletal rehabilitation physiotherapy. Furthermore, they have the potential to improve the quality of physiotherapy care.